Sex-associated differences in trace metals concentrations in and on the plumage of a common urban bird species - Frantz, Adrien (Ecotoxicology (London, England), 2016)
Urban areas encompass both favorable and stressful conditions linked with human activities and pollution. Pollutants remain of major ecological importance for synanthropic organisms living in the city. Plumage of urban birds harbour trace metals, which can result from external deposition or from internal accumulation. External and internal plumage concentrations likely differ between specific trace metals, and may further differ between males and females because of potential sex-linked differential urban use, physiology or behaviour. Here, we measured the concentrations in four trace metals (cadmium, copper, lead and zinc) in both unwashed and washed feathers of 49 male and 38 female feral pigeons (Columba livia) from Parisian agglomeration. We found that these concentrations indeed differed between unwashed and washed feathers, between males and females, and for some metals depended on the interaction between these factors. We discuss these results in the light of physiological and behavioural differences between males and females and of spatial repartition of the four trace metals in the city